(untitled) (Baghdad Science Journal, 2025)
Sb2S3 thin films have been prepared by chemical bath deposition on a glas sub Absorbance and transmittance spectra were recorded in the wavelength range (30-900) nm. The effects of thickness on absorption coefficient, reflectance, refractive index, extinction coefficient, real and imaginary parts of dielectric constant were estimated. It was found that the reflectivity, absorption coefficient , extinction coefficient, real part of dielectric constant and refractive index, all these parameters decrease as the thickness increased, while the imaginary part of the dielectric constant increase as the thickness increased.